Corn Cob-Derived Activated Carbon for Chloramphenicol Removal: An Optimization and Mass Transfer Model Study - Mohamad Razif Mohd Ramli; Abdul Wahab Mohammad; Mohd Sobri Takriff; Mohd Azmier Ahmad; Noor Fazliani Shoparwe; Ebenezer I. Oluwasola (Emerging Science Journal, 2026)
This study developed a sustainable activated carbon (AC) from corn cob agricultural waste for efficient chloramphenicol (CP) removal from aqueous solutions and to improve the predictive understanding of the adsorption process. Microwave-assisted physicochemical activation using potassium hydroxide (KOH) was optimized through response surface methodology (RSM), with activation time, microwave radiation power, and impregnation ratio (IR) identified as the key preparation variables. Under the optimal conditions (3.86 min, 616 W, and 2.5 g/g), the resulting AC achieved a yield of 16.6% and a CP adsorption capacity of 20.2 mg/g. The optimized AC exhibited a high BET surface area (832.68 m²/g), a mesopore-dominated pore structure (mesoporous surface area of 623.45 m²/g), a pore volume of 0.09067 cm³/g, and an average pore diameter of 1.93 nm, leading to a maximum experimental adsorption capacity of 20.68 mg/g at 30 °C. In addition, a mass transfer (MT) model was successfully applied to predict an equilibrium adsorption capacity of 21.48 mg/g with a low average error of 3.29% and R² ≥ 0.90. By integrating process optimization with mass transfer modeling, this study improves the understanding of CP adsorption and provides a practical framework for designing efficient, waste-derived adsorbents for antibiotic-contaminated water treatment.